2006
DOI: 10.1213/01.ane.0000194587.94260.1d
|View full text |Cite
|
Sign up to set email alerts
|

The Additive Antinociceptive Interaction Between WIN 55,212-2, a Cannabinoid Agonist, and Ketorolac

Abstract: Combinations of nonsteroidal antiinflammatory drugs (NSAIDs) and opioids are widespread in the management of pain, allowing better analgesia with reduced side effects. Cannabinoids are promising analgesic drugs that have pharmacological properties similar to those of opioids. However, the beneficial effects of cannabinoids for pain treatment are counterbalanced by their psychotomimetic side effects. We designed the present study to evaluate the antinociceptive interaction between cannabinoids and NSAIDs in mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
29
1
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 24 publications
6
29
1
4
Order By: Relevance
“…Ketorolac is highly bound to human plasma protein (mean 99.2%). There is no evidence in animal or human studies that ketorolac tromethamine induces or inhibits hepatic enzymes capable of metabolizing itself or other drugs [18].…”
Section: Discussionmentioning
confidence: 99%
“…Ketorolac is highly bound to human plasma protein (mean 99.2%). There is no evidence in animal or human studies that ketorolac tromethamine induces or inhibits hepatic enzymes capable of metabolizing itself or other drugs [18].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous early studies have also demonstrated beneficial effects of cannabinoids in animal models of pain (reviewed in Fox and Bevan, 2005). In acute pain, anandamide, THC, cannabidiol, and synthetic cannabinoids such as CP55,940 and WIN 55,212-2 are effective against chemical ( Sofia et al, 1973;Formukong et al, 1988;Calignano et al, 1998;Costa et al, 2004a,b;Ulugol et al, 2006), mechanical (Sofia et al, 1973;Martin et al, 1996;Smith et al, 1998;, and thermal pain stimuli (Buxbaum, 1972;Bloom et al, 1977;Lichtman and Martin, 1991a,b;Fride and Mechoulam, 1993;. Recent animal studies indicate that anandamide and cannabinoid ligands are also very effective against chronic pain of both neuropathic (Herzberg et al, 1997;Bridges et al, 2001;Fox et al, 2001;) and inflammatory origin (Tsou et al, 1996;Richardson et al, 1998a,b,c;Li et al, 1999;Martin et al, 1999b;.…”
Section: B Pain and Inflammationmentioning
confidence: 99%
“…Recent animal studies indicate that anandamide and cannabinoid ligands are also very effective against chronic pain of both neuropathic (Herzberg et al, 1997;Bridges et al, 2001;Fox et al, 2001;) and inflammatory origin (Tsou et al, 1996;Richardson et al, 1998a,b,c;Li et al, 1999;Martin et al, 1999b;. Moreover, endocannabinoids and synthetic cannabinoids exert synergistic antinociceptive effects when combined with commonly used nonsteroid anti-inflammatory drugs, which may have utility in the pharmacotherapy of pain Ulugol et al, 2006). Interestingly, a recent study has implicated the endocannabinoid system in the analgesic activity of paracetamol (acetaminophen), the most widely used painkiller (Ottani et al, 2006), and there is also evidence for endocannabinoid involvement in the action of some general anesthetics, such as propofol Schelling et al, 2006).…”
Section: B Pain and Inflammationmentioning
confidence: 99%
“…Combining low doses of cannabinoids with other analgesics, such as opioids or NSAIDs, is also promising. Reducing the cannabinoid and opioid/NSAID dose needed may provide an advantageous treatment strategy by enhancing pain relief whilst minimising the incidence of adverse effects (6,7,37). Elevating endocannabinoid levels appears to be the most striking strategy for developing analgesic drugs with cannabinoid properties but devoid of central psychotropic effects (38)(39)(40).…”
Section: Modulation Of the Endocannabinoid Systemmentioning
confidence: 99%
“…-tetrahydrocannabinol (THC) and cannabidiol, the critical components of the cannabis plant, and the synthetic cannabinoids and their analogues have been shown to exert strong analgesic action both in preclinical and clinical studies (6)(7)(8)(9). In this review, after a brief introduction to cannabinoid receptors, phytocannabinoids and synthetic cannabinoids, I provide an overview of what is currently known about the synthesis, release, degradation and biological actions of endocannabinoids, regarding their role in pain modulation, and describe the recent evidence of the promising results of augmentation of endogenous cannabinoid tonus for the treatment of pain.…”
mentioning
confidence: 99%